Relationship between activity and stability: Design and characterization of stable variants of human frataxin - Castro, Ignacio Hugo (2020)
The relationships between conformational dynamics, stability and protein function are not obvious. Frataxin (FXN) is an essential protein that forms part of a supercomplex dedicated to the iron-sulfur (Fe–S) cluster assembly within the mitochondrial matrix. In humans, the loss of FXN expression or a decrease in its functionality results in Friedreich's Ataxia, a cardio-neurodegenerative disease. Recently, the way in which FXN interacts with the rest of the subunits of the supercomplex was uncovered. This opens a window to explore relationships between structural dynamics and function. In this study, we prepared a set of FXN variants spanning a broad range of conformational stabilities. Variants S160I, S160M and A204R were more stable than the wild-type and showed similar biological activity. Additionally, we prepared SILCAR, a variant that combines S160I, L203C and A204R mutations. SILCAR was 2.4 kcal mol−1 more stable and equally active. Some of the variants were significantly more resistant to proteolysis than the wild-type FXN. SILCAR showed the highest resistance, suggesting a more rigid structure. It was corroborated by means of molecular dynamics simulations. Relaxation dispersion NMR experiments comparing SILCAR and wild-type variants suggested similar internal motions in the microsecond to millisecond timescale. Instead, variant S157I showed higher denaturation resistance but a significant lower function, similarly to that observed for the FRDA variant N146K. We concluded that the contribution of particular side chains to the conformational stability of FXN might be highly subordinated to their impact on both the protein function and the stability of the functional supercomplex.